A Strategic Approach to Technological Innovation Capability and Marketing Mix Orientation for Achieving Human Resource Performance in the Retail Industry (International Forum of Researchers and Lecturers, 2025)
This study explores a strategic approach that integrates technological innovation capability and marketing mix orientation to enhance human resource (HR) performance in the retail industry. The research is motivated by the growing demand for adaptive HR strategies in response to the rapid technological transformations and competitive market dynamics faced by retail businesses. Despite the abundance of studies focusing on either innovation or marketing practices separately, limited attention has been given to how both dimensions synergize to influence HR performance, particularly in the context of emerging markets. The research employs a qualitative methodology with a case study approach, focusing on selected retail companies in Indonesia. Data were collected through in-depth interviews with key managerial personnel, supported by documentation and field observations. Thematic analysis was used to interpret the data and identify critical patterns and interrelationships among variables. The findings reveal that the alignment of technological innovation capabilities with a proactive marketing mix orientation leads to improved HR adaptability, motivation, and productivity. The study also highlights the role of strategic leadership in facilitating this integration and fostering an innovation-driven organizational culture. Additionally, it identifies contextual enablers such as digital infrastructure and market responsiveness as essential components for maximizing HR performance outcomes. The study concludes that a comprehensive strategic approach combining innovation and marketing orientations is vital for sustaining HR excellence in the evolving retail landscape. These insights offer practical implications for retail leaders and HR practitioners aiming to future-proof their workforce through integrated strategic initiatives.